PENEGAKAN HUKUM TERHADAP PENELANTARAN ANAK DI KABUPATEN KENDAL - Wijayati, Safriena Rudy; Listyarini, Dyah (Collegium Studiosum Journal, 2023)
Abandoned children is a child who has not yet turned 18 (eighteen) years old and for some reason one or both parents are unable to fulfill their child's rights to grow and develop, then in the end they became abandoned. Article number 34 section one (1) of the 1945..Constitution of Republic Indonesia..states that "Impoverished persons and abandoned children shall be taken care of by the State". Through this article state that abandoned children's lives are protected by the state such as the needs of clothing, food and place. This thesis will discuss about law enforcement against child neglect in Kendal Regency, and aims to find out what law enforcement has been carried out by the Kendal Regency Social Service in dealing with violations of Article 34 of the 1945 Constitution concerning abandoned children in Kendal Regency. There are several factors that encourage children to be abandoned, the first is due to difficult economic conditions, disharmonious household, and internal factors. The research method for this thesis is a descriptive qualitative approach. The data was come from collected through in-depth of interviews and observation with the informants. The main informant in this research was the Head of the Kendal Regency Social Rehabilitation Division, and the additional informant was 1 (one) abandoned child. While secondary data obtained through various sources of literature, namely books, journals, or electronic media. As a result, the Kendal Regency Social Service has made efforts to ensure the lives of abandoned children, such as fostering street childrens, registering and sending them to social institutions, and providing disability assistance for abandoned children with special needs.